Analisis Kualitas Pelayanan dan Usulan Perbaikan Pelayanan Travel Malang-Bandara Juanda - Muhammad Nasri (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
The existence of travel agency in Malang is viewed as strategic business because it could replace the personal vehicle for heading toward Juanda Airport in Surabaya since Malang itself didn't have any international standard airport so the member of the society who wants to get in or out from Malang using aeroplane should go to Juanda Airport in Surabaya. This would cause the competition among travel services in Malang become more competitive by the emerging of new travel agencies. In case the Kirana Travel Agency would maintain its existence, they need to make efforts to improve its service quality. Therefore, it require an experiment to found out what kind of service attributes that wanted by the customer and how does the gap between the perception and consumer expectancy toward the ongoing service quality. One of the planning method that can be use to translate the need of the consumer into action plan for the company is QFD. This step would be use as evaluation tool and planning on service quality improvement. To sharpened identification of the service quality attributes then the QFD approach integrated with Servqual approach. During the Servqual review, it is found eight service attributes that need to be fixed which is: information accuracy given by the employees, the precise time on pick-up, good reaction of the employees in handling consumer complaints, the availability of health and safety facility (First aid box, fire extinguisher, etc), travel order confirmation, driver that should consistently being polite toward the consumer, easy access to be called and gain information from the operator and travel prices. While the technical response prioritized to be fix and to be use for fulfilling the consumer satisfaction in Kirana Travel from the HOQ analysis includes: employees training (contributed 23.43%), providing special number for complain support (contribution 13.71%), fixing the communication inter-department inside the company (contribution 11.84%), fixing the pick-up schedule system (contribution 8.83%). The improvement proposal given by the researcher is to improve the new and old employee training so it could bring better performance in order to fulfilling the consumer satisfaction.